2013
DOI: 10.1007/bf03341676
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Ambulatory Team Observed Structured Clinical Evaluation (ATOSCE)

Abstract: In response to the call for tools to measure collaboration in interprofessional settings, an Ambulatory Team Observed Structured Clinical Evaluation (ATOSCE) was developed to measure collaboration/teamwork behaviors and skills in a realistic simulation for graduate students in the healthcare professions. Participants rated the ATOSCE a realistic and valuable learning experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The outpatient scenario challenged learners to place the patient at the center of the health care team, to include the caregiver on that team, and to work collaboratively with other health care providers while employing conflict management skills. 13 After the simulation, the SP and standardized family member debriefed the learner, and learners then met together for a group debriefing.…”
Section: Simulation Scenario and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The outpatient scenario challenged learners to place the patient at the center of the health care team, to include the caregiver on that team, and to work collaboratively with other health care providers while employing conflict management skills. 13 After the simulation, the SP and standardized family member debriefed the learner, and learners then met together for a group debriefing.…”
Section: Simulation Scenario and Proceduresmentioning
confidence: 99%
“…Feedback has indicated that learners participating in this simulation find it to be realistic and conducive to using their collaboration skills. 13 Learners were provided with a written overview of the purpose of the simulation (see Text Document, Supplemental Digital Content 2, http://links.lww.com/SIH/A218, brief overview of the ATOSCE methods), and a simulation staff member provided general verbal instructions (see Text Document, Supplemental Digital Content 3, http://links.lww.com/SIH/A219, procedures and time durations for the simulation). Learners did not know the particulars of the case or assessment instrument until beginning the simulation, when they picked up the information hanging on the doorway, consisting of a written description of the SPs who would be entering the room (see Text Document, Supplemental Digital Content 4, http://links.lww.com/SIH/A220, setting, presenting situation and patient's hospital discharge summary).…”
Section: Simulation Scenario and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Students receive similar cases in a standardized patient (SP) setting for the next level of IPE/IPCP application. IPCP simulations with SPs help bridge the gap for students who have not yet had a rigorous level of patient care in their curriculum 15 . These SP experiences would include providing written referrals and oral communication with the chosen team member(s) based on the patient scenario.…”
Section: Bridging the Gap Between Ipe And Ipcpmentioning
confidence: 99%